First 40Ar/39Ar analyses of Australasian tektites in close association with bifacially worked artifacts at Nalai site in Bose Basin, South China: The question of the early Chinese Acheulean. Issue 153 (April 2021) - Michel, Véronique; Feng, Xiaobo; Shen, Guanjun; Cauche, Dominique; Moncel, Marie-Hélène; Gallet, Sylvain; Gratuze, Bernard; Wei, Jiang; Ma, Xiaorong; Liu, Kangti
Abstract: The recently discovered Nalai site is one of the Bose Basin localities, which is key to studying the earliest bifaces in China. The Nalai site has yielded an abundance of lithic artifacts, including bifaces and tektites in close association. The total fusion 40 Ar/ 39 Ar method was applied to four tektites discovered beside and contemporaneous with bifaces in the red laterite sediments of the upper levels of the T4 terrace (layers 4 and 5). Our 40 Ar/ 39 Ar data with a weighted mean age of 809 ± 12 ka provide for the first time unequivocal dates for bifacial production at Bose, broadly consistent with the precise Australasian tektite age of 788.1 ± 2.8 ka, recently published by other investigators. The relatively important errors reported here suggest sample contamination by clasts or bubbles for the oldest aliquots and alteration for the younger ones. The lithic assemblage from layers 4 and 5 of the Nalai site is quite similar to that found at other sites in the Bose Basin. The assemblages are dominated by choppers, but bifaces, picks, and unifaces give a Mode 2 and Acheulean-type character to the series. The high frequency of the round tongue-shaped tip, a low elongation index, and a wide and thick base characterize the Large Cutting Tools. These results contribute to resolving ongoing debates on the timing and origin of bifaces and the Acheulean in China.